Islamic Science in the late Abbasid (945-1258) - Islam, Arshad (2015)
Islamic knowledge during the Middle Ages is well known, integrating natural sciences, mathematics, theology and philosophy, as Muslims studied and learned from others’ expertise and civilizations as well as producing important original works. The Abbasid-era contribution of Muslims to the individual disciplines of science such as medicine, mathematics, astronomy, geometry, geology, mineralogy, chemistry, philosophy, architecture and trigonometry are particularly remarkable in the history of Islamic civilization. This paper highlights those aspects of Muslims’ contribution to the scientific body of knowledge that are subtle and perhaps more important to the development of science as a whole. They examined critically, collated, corrected and significantly enriched major texts of Greek science and philosophy. The translation phase of Muslim scientific activity (from Greek) was undertaken during the early Abbasid period, while the later Abbasid period witnessed the most substantial original contributions of Muslim scientists to civilization, which was ongoing despite the political weakness of the later Abbasids, and the turbulence of west and central Asia during that period. Through an analysis of socio-cultural and historical contexts, this paper concludes that the contribution of Muslim scientists during the late Abbasid period to lay (a) in contributing innovative knowledge and research to the body of the sciences; and (b) in bringing to the knowledge of Europe their own researches and the works of Indian men of science, especially in mathematics, astronomy and medicine. Based mainly on Arabic, Persian, Urdu and English sources, the study focuses on the intellectual legacy of the Muslims, their interest in the progress of science and philosophy and the impact of Muslim science on modern scientific heritage. Keywords: Abbasids, medicine, mathematics, astronomy, geometry, geology, mineralogy, chemistry, philosophy, Islamic civilization